Current trends in trichloroethylene biodegradation: A review - Shukla A.K.; Upadhyay S.N.; Dubey S.K. (My University, 2025)
Over the past few years biodegradation of trichloroethylene (TCE) using different microorganisms has been investigated by several researchers. In this review article, an attempt has been made to present a critical summary of the recent results related to two major processes - reductive dechlorination and aerobic co-metabolism used for TCE biodegradation. It has been shown that mainly Clostridium sp. DC-1, KYT-1, Dehalobacter, Dehalococcoides, Desulfuromonas, Desulfitobacterium, Propionibacterium sp. HK-1, and Sulfurospirillum bacterial communities are responsible for the reductive dechlorination of TCE. Efficacy of bacterial communities like Nitrosomonas, Pseudomonas, Rhodococcus, and Xanthobacter sp. etc. for TCE biodegradation under aerobic conditions has also been examined. Mixed cultures of diazotrophs and methanotrophs have been used for TCE degradation in batch and continuous cultures (biofilter) under aerobic conditions. In addition, some fungi (Trametes versicolor, Phanerochaete chrysosporium ME-446) and Actinomycetes have also been used for aerobic biodegradation of TCE. The available information on kinetics of biofiltration of TCE and its degradation end-products such as CO2 are discussed along with the available results on the diversity of bacterial community obtained using molecular biological approaches. It has emerged that there is a need to use metabolic engineering and molecular biological tools more intensively to improve the robustness of TCE degrading microbial species and assess their diversity. © 2014 Informa Healthcare USA, Inc.